Working-Class Experience: The Rise and Reconstitution of Canadian Labour, 1800-1980 - White, Jerry P. (Relations Industrielles / Industrial Relations, 1985)
This article reviews the book, "Working-Class Experience : The Rise and Reconstitution of Canadian Labour, 1800-1980," by Bryan Palmer.